Editorial (American Journal of Islam and Society, 2009)
In his capacity as president of the Islamic Republic of Pakistan, on 13 April2009AsifAli Zardari signed an ordinance (Nizam-e-Adl Regulation) imposingShari`ah law on the Swat Valley. Although approved by the PakistaniNational Assembly,1 analysts believe this measure will embolden theTaliban’s already increasing strength in and around that region. Some humanright groups also fear that the Taliban will see this decision as a license tosend the region’s people back to the “Dark Ages" (whatever that maymean).2 These reactions are not new.It may be quite tempting to ask why the Shari`ah is so abhorrent to itsopponents and why implementing it is so attractive to those Muslims whoare bent on applying it. Frankly put, although the mere mention of such aprospect evokes both emotions, to the majority of practicing Muslims evenposing such questions affronts their religious sensibilities. However, is thecurrent reaction truly about the Shari`ah’s essence and application, or aboutwhat the Taliban will make of it? Yes, the maddening and egregious behaviorof the Taliban and other extremist elements render almost everythingabout Islam (especially the Shari`ah) terrifyingly repulsive.But in this era of information explosion, it is the responsibility of theworld’s “civilized” people, regardless of religion, to inform themselves, inan honest and sincere manner, about the Shari`ah’s contents (not that doingso would absolutely guarantee its positive or fair consideration) in order toavoid any “hair-splitting” whenever its application is proposed.Whose faultis it if people fail to distinguish between the likes of the Taliban (who areunable to understand the Shari`ah’s real reasons and wisdom, even if theyhave the utmost zeal to apply them) and the actual Shari`ah (which, themajority ofMuslims believe, exists only to protect and guide people in theirlives and does not impose on them anything beyond their capability)? ...